Determinants of quality-based payments for livestock in conflict-prone areas in Kenya. (May 2022) - Mugonya, John; Hauser, Michael
Abstract: The mechanisms influencing livestock pricing in Kenya are well studied. The determinants of quality-based payments on markets in conflict-affected areas, however, are hardly documented. In this paper, we offer a deeper understanding of transitions towards quality-based payments from the perspective of livestock buyers in the Kerio-Valley, Kenya. The location is known for protracted communal conflicts. Transcripts from qualitative interviews, focus group discussions and field notes from participant observation we coded and analysed using MAXQDA. Our data identify three broad determinants (chain organisation and financing, market system development, quality and value of livestock) relevant for the transition from traditional to quality-based payments for livestock in conflict prone drylands. We then discuss the standard definition of livestock quality by market players, the behaviours of traders, and market institutions as entry points to leverage transitions to quality-based payments in future. Also, seasonal changes and security perceptions influence the potential for introducing quality-based payments. Although limited to the Kerio-Valley, key insights we offer could apply to similar conflict-prone settings in the region. Highlights: Quality-based payments for livestock drylands could contribute to peacebuilding. Value chain organisation and financing supports quality-based payments. Market system development will be essential for quality-based payments. Quality and value of livestock requires redefinition.